“Barru Membaca” sebagai Gerakan Literasi Alternatif; Studi tentang Pembudayaan Literasi Membaca pada Masyarakat di Kabupaten Barru, Provinsi Sulawesi Selatan - Askar Nur; Muhammad Syamsul Abdullah (Kementerian Koordinator Bidang Pembangunan Manusia dan Kebudayaan Republik Indonesia, 2022)
Currently, technological developments have significant impact on people's lives. This development must also be followed by the mentality and readiness of the community to deal with it. One form of effort to keep pace with technological developments is through literacy-based community empowerment. This research focuses on community empowerment through cultivating reading literacy as a step in facing the challenges of the times while creating quality community characters based on literacy skills. Aspects of discussion in this research are alternative literacy movement carried out by the Barru Membaca community in the process of cultivating reading literacy among the people of Barru District, Barru Regency, South Sulawesi Province and responds of the community to the presence of the Barru Membaca community. This research uses descriptive research with a qualitative approach by conducting interviews with informants. The data analysis technique used is data collection, reduction, data presentation and drawing conclusions. The results showed that the process of cultivating reading literacy carried out by the Barru Membaca community had been running systematically, efficiently and independently, starting from the planning process of reading literacy acculturation programs, to the program evaluation stage in improving human resources literacy skills.